Chapter Fototesti di viaggio: Absolutely nothing di Giorgio Vasta e Ramak Fazel - Fastelli, Federico (Studi e saggi, 2021)
The essay examines the travel photo-text genre from a theoretical point of view, through the example of Absolutely Nothing by Giorgio Vasta and Ramak Fazel. It discusses the key issues and perspectives within the theory and methodology of visual studies and visual culture and describes the opposition between the verbal and visual parts of the volume, understood as a "Struggle for Territory". This puts on strain the foundations of the travel story tradition, such as the narrative authentication.